Mixed ZnSxSe₁-x crystals for digital radiography detectors - Trubaieva, O.G.; Chaika, M.A.; Paszkowicz, W. (Functional Materials, 2018)
A possibility to use ZnSxSe₁-x as a material for detection of X-ray and alpha particles has been studied. The influence of the sulphur content on the properties of ZnSxSe₁-x crystals is analyzed. The bulk ZnSxSe₁-x crystals were obtained by Bridgman-Stockbarger method. Six different plates cut off from the crystals with x from 0.07 to 0.39 were studied. It is found that intensity of X-ray luminescence spectra of ZnSxSe₁-x plates increases with increasing sulfur content, reaching the maximum value for ZnS₀.₂₂Se₀.₇₈ composition. The scintillation light output of ZnSxSe₁-x plates is shown to be higher than for commercial ZnSe(Te) and ZnSe(Al) crystals.